2015
DOI: 10.1515/cclm-2014-0583
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Improvacuter™ tubes with BD Vacutainer™ tubes for various hormones in the aspects of stability and influence of gel separators

Abstract: Gel containing tubes (both BD and Improve) gave comparable results with the tubes which do not contain gel except for estradiol and testosterone. The use of gel containing tubes for estradiol and testosterone are not recommended on UniCel® DxI 800 according to our results. The change in the analyte concentrations over 48 h remained within the TEA limits for the studied analytes. Improve tubes gave similar results to BD tubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…2,7,8 Conventional methods such as a vacutainer system, ultra-filtration, and commercial kits are used for DNA extraction. [9][10][11][12] Although traditional DNA extraction methods have advantages, they are restricted in their application in point-of-care (POC) diagnostic platforms owing to their high cost, time consumption, and need for a well-trained professional to operate the equipment. Thus, to obtain high-quality DNA for utilization in resourcelimited areas, DNA extraction techniques with portable settings are essential.…”
Section: Doctormentioning
confidence: 99%
“…2,7,8 Conventional methods such as a vacutainer system, ultra-filtration, and commercial kits are used for DNA extraction. [9][10][11][12] Although traditional DNA extraction methods have advantages, they are restricted in their application in point-of-care (POC) diagnostic platforms owing to their high cost, time consumption, and need for a well-trained professional to operate the equipment. Thus, to obtain high-quality DNA for utilization in resourcelimited areas, DNA extraction techniques with portable settings are essential.…”
Section: Doctormentioning
confidence: 99%
“…comparative tubes) to verify the manufactures claims. This approach has been proven by the constantly growing number of studies in all areas of diagnostic testing [9][10][11][12], including molecular biology [13,14].…”
Section: Essential Requisite For Purchasing Blood Collection Devicesmentioning
confidence: 99%
“…They concluded that aforementioned materials had not any adverse effect on these analytes. Zungun et al [20] compared the effect of two commercial SST's, named improvacuter and BD vacutainer with SST without gel for various hormones in the aspects of stability and influence of gel separators. They reached to this point that all SST's had more or less the same chemical test results with the exception for two hormones, Estradiol and Testosterone.…”
Section: Introductionmentioning
confidence: 99%